The Maravijaya of Buddha and the Image of Pārśvanātha. Paralellism of Buddhist and Jain Iconography of Ancient India - Vorobyeva, Darya N. (Actual Problems of Theory and History of Art, 2019)
The report deals with similar compositional schemes in the art of different religions of AncientIndia on the example of two iconographic schemes: Triumphing Buddha over Mara (Maravijaya or “Temptation of the Buddha by the demon Mara”) and the temptation of Pārśvanātha by the demon Meghmal. With varying degrees of detail, this plot is presented in the iconographic program of various Indian temple complexes.The plot of these two scenes — Buddhist and Jaina — is similar: the demonic forces are trying to get the meditating ascetic out of his concentration, to break down in various ways, preventing enlightenment. Demonic figures, located around a large central figure, are the personifications of various passions with which a person who chooses an ascetic feat has to fight. An important feature of the compositions analysed in the report is the presence of images of musicians playing different instruments. The value of these images will be paid special attention. Historically, the development of the art of the three major religions of early medieval India went in parallel (Buddhism, Hinduism, Jainism). Temples of different religions often coexisted in one complex, the most striking example being the rock-cut complex of Ellora, where Buddhists, Jains and Hindu coexisted during centuries in early medieval period. In the first centuries B.C. in Mathura, temples of Buddhists, Jains, Shaivites,Vishnuites, and even admirers of the Nagas were neighbours; in Badami and Aihole, Jain temples coexist with Hindu sanctuaries. If you look at the Jaina reliefs of the cave temples of Udaigiri and Khandagiri of Orissa, you can see that they bear the imprint of the pictorial tradition of the Buddhist monuments of Sanchi and so on.The choice of the same composite schemes for the realization of similar ideas is a characteristic feature of Indian art of the time of religious iconography formation, when successfully found solutions were borrowed,migrating from one religion to another. This concerns not only visual art, but also architecture.